Intestinal fungi biogeography, succession and its association with diarrhea in pigs - Ruochen Ren; Xiaojun Zhang; Fangfang Lou; Yang Li; Lingyan Ma; Yingping Xiao; Qu Chen; Yang Wen; Wentao Lyu (Journal of Animal Science and Biotechnology)
Abstract Background The composition and relative abundances of intestinal microbiota are closely related to animal growth, development and health. This study provides a comprehensive analysis of the spatial distribution and temporal dynamics of intestinal fungi in pigs, with a focus on fungal alterations associated with diarrhea. Methods Intestinal digesta from duodenum, jejunum, ileum, cecum, colon and feces of 8 finishing pigs (180 days old) were collected. Fecal samples were also collected from 18 pigs across different growth stages, including lactation (3 d), nursery (26 d, 35 d, 49 d), growing (120 d) and finishing (180 d). Additionally, feces were collected from 32 diarrheal and 32 healthy piglets at 28 days old. Fungal community profiling in these samples was performed using internal transcribed spacer (ITS) sequencing. Results A total of 9,224 amplicon sequence variants (ASVs) were detected in all of 220 samples. Intestinal fungal diversity exhibited clear biogeographic patterns, with significantly lower richness and Shannon index in the ileum (P < 0.05) and significantly higher richness in the large intestine and feces (P < 0.05). The fungal community structure also varied significantly across intestinal segments, with Kazachstania dominating in the ileum and Geotrichum in the duodenum and jejunum. Across growth stages, fecal fungal diversity increased after weaning. PCoA results revealed that fungal structure exhibited significant temporal changes (R = 0.7313, P = 0.001), with the core fungal taxa dominated by Diutina catenulata, Aspergillus restrictus and Tahromyces munnarensis. In addition, by comparing the fungal community of piglets with and without diarrhea, the richness and Shannon index were significantly higher in the diarrheal piglets than those in healthy piglets (P < 0.05) with Kazachstania, Diutina and Aspergillus enriched in diarrheal piglets and Geotrichum, Tahromyces and Piromyces in healthy piglets. Conclusions The intestinal fungal community in pigs shows distinct spatial variation, with greater diversity in the large intestine. Fungal composition shifts dynamically with age, particularly around the weaning transition. This study highlights specific fungal taxa associated with diarrhea caused by weaning stress, offering new insights into the interplay between gut fungi and pig health.